2019
DOI: 10.1002/ppul.24427
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the need for adenotonsillectomy for sleep‐disordered breathing in a community setting: A secondary outcome measures analysis of a randomized controlled study

Abstract: Objective To assess whether children with sleep‐disordered breathing (SDB) symptom severity above a certain level, measured by a validated questionnaire, improve after adenotonsillectomy (AT) compared to no intervention. Methods Children with snoring and tonsillar hypertrophy (4 to 10‐years old), who were candidates for AT, were randomly assigned to two evaluation sequences (baseline and 3‐month follow‐up): (a) evaluation immediately before AT and at 3 months postoperatively (AT group); or (b) evaluation at th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 35 publications
0
0
0
Order By: Relevance
“…Surgeons should take into consideration demographic factors, baseline AHI, and the propensity of weight gain when counseling and managing expectations about postoperative outcomes and be prepared to introduce adjunctive treatments for OSA. This study corroborated previous retrospective studies 17 and meta-analyses, 4 by demonstrating that that AT remains an effective treatment option for significantly mitigating pediatric OSA, as 86.0% of our cohort achieved an AHI value of less than 5. Current theories about the reasons for postoperative weight gain include reduced Recent studies have shown that postsurgical weight gain after tonsillectomy lasts anywhere between 7 and 24 months.…”
Section: Discussionsupporting
confidence: 90%
“…Surgeons should take into consideration demographic factors, baseline AHI, and the propensity of weight gain when counseling and managing expectations about postoperative outcomes and be prepared to introduce adjunctive treatments for OSA. This study corroborated previous retrospective studies 17 and meta-analyses, 4 by demonstrating that that AT remains an effective treatment option for significantly mitigating pediatric OSA, as 86.0% of our cohort achieved an AHI value of less than 5. Current theories about the reasons for postoperative weight gain include reduced Recent studies have shown that postsurgical weight gain after tonsillectomy lasts anywhere between 7 and 24 months.…”
Section: Discussionsupporting
confidence: 90%